2009
DOI: 10.1016/j.geb.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in viscous populations—Experimental evidence

Abstract: We experimentally investigate the effect of population viscosity (an increased probability to interact with others of one's type or group) on cooperation in a standard prisoner's dilemma environment. Subjects can repeatedly choose between two groups that differ in the defector gain in the associated prisoner's dilemma. Choosing into the group with the smaller defector-gain can signal one's willingness to cooperate. We find that viscosity produces an endogenous sorting of cooperators and defectors and persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 23 publications
5
39
0
Order By: Relevance
“…Our experimental evidence only partially confirms and points to a perceived reduction in uncertainty as a main motive for homophily (see below). A number of papers have considered social dilemma games with an endogenous group structure (Coricelli et al, 2004;Keser and van Winden, 2000;Grimm and Mengel, 2009;Ahn et al, 2009 among others). Since selection and exclusion -that are indeed found to affect behaviour -are based on behaviour rather than group membership or identity in these studies, they are somewhat less related to our work.…”
mentioning
confidence: 99%
“…Our experimental evidence only partially confirms and points to a perceived reduction in uncertainty as a main motive for homophily (see below). A number of papers have considered social dilemma games with an endogenous group structure (Coricelli et al, 2004;Keser and van Winden, 2000;Grimm and Mengel, 2009;Ahn et al, 2009 among others). Since selection and exclusion -that are indeed found to affect behaviour -are based on behaviour rather than group membership or identity in these studies, they are somewhat less related to our work.…”
mentioning
confidence: 99%
“…The subjects then played an Nperson prisoner's dilemma game, where N is the community size that selected the same payoff matrix. Grimm and Mengel (2009) found that subjects cooperate significantly more when they sacrifice the defector gains. These past studies are different from our study with two important aspects.…”
Section: Hypothesis 3(e): the Percentage Of Subjects That Sort Into Tmentioning
confidence: 94%
“…They found that the centralized sanctioning institution and an informal sanctioning institution are most frequently chosen and subjects can achieve higher cooperation with these institutions. 16 Lastly, Grimm and Mengel (2009) let subjects choose one out of two payoff matrices. With one of the two payoff matrices, a subject would have not only less temptation to defect but also a less mutual defection payoff.…”
Section: Hypothesis 3(e): the Percentage Of Subjects That Sort Into Tmentioning
confidence: 99%
“…Our experimental evidence only partially confirms and points to a perceived reduction in uncertainty as a main motive for homophily (see below). A number of papers have considered public goods experiments with an endogenous group structure (Coricelli, Fehr, and Fellner (2004), Keser and van Winden (2000), Grimm and Mengel (2009) and Ahn and Salmon (2009) among others). Since selection and exclusion -that are indeed found to affect behaviour -are based on behavior rather than group membership or identity in these studies, they are somewhat less related to our work.…”
Section: Related Literaturementioning
confidence: 99%